2001
DOI: 10.1159/000053725
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-Induced Activation of Human Lung Macrophages

Abstract: Background: Histamine plays a central role in the pathogenesis of allergic and inflammatory diseases by modulating vascular and airway responses. Increasing evidence suggests that histamine also regulates the function of inflammatory and immune cells. Macrophages are primarily involved in inflammatory diseases of the lung. We explored the ability of low concentrations of histamine to induce the release of proinflammatory mediators from human lung macrophages. Methods: Macrophages purified (>95%) from lung pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…As an example, in line with our observations, histamine via H2R, has been shown to inhibit the cytokine response to microbial products of monocytes [28,32] and dendritic cells [33]. Differentiation of monocytes into macrophages, on the other hand, induces the preferential expression of H1R over H2R [34], leading to increased production of IL-8 upon exposure to histamine [35]. Therefore, the response to histamine can greatly vary among different cells, depending on expression profile of histamine receptors and among different individuals, possibly depending on genetic variation of histamine receptors [36].…”
supporting
confidence: 86%
“…As an example, in line with our observations, histamine via H2R, has been shown to inhibit the cytokine response to microbial products of monocytes [28,32] and dendritic cells [33]. Differentiation of monocytes into macrophages, on the other hand, induces the preferential expression of H1R over H2R [34], leading to increased production of IL-8 upon exposure to histamine [35]. Therefore, the response to histamine can greatly vary among different cells, depending on expression profile of histamine receptors and among different individuals, possibly depending on genetic variation of histamine receptors [36].…”
supporting
confidence: 86%
“…20,22,33 The effect of fexofenadine on nasal congestion might reflect an activity that is broader than its antagonism at the H 1 -receptor. Numerous in vitro studies with fexofenadine have highlighted the potential of this agent to produce significant anti-inflammatory effects at clinically relevant concentrations, [34][35][36][37][38] and it is hypothesized that these effects might contribute to inhibition of the late-phase response. 37 In this large pediatric population, the incidence and severity of reported adverse events with fexofenadine were similar to those for placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Fexofenadine is a potent, selective, non-sedating, H 1 -receptor antagonist with proven efficacy in the relief of clinical symptoms of AR, including nasal congestion [11, 12, 13, 14, 15, 16, 17, 18]. In addition to its anti-allergic effects, fexofenadine has anti-inflammatory properties at clinically relevant concentrations [19, 20, 21]. Furthermore, health outcome studies have shown that fexofenadine HCl 60 mg twice daily (b.i.d.)…”
Section: Introductionmentioning
confidence: 99%